Therapeutic Ultrasound-Enhanced Immune Checkpoint Inhibitor Therapy - Yuan, Jinyun; Ye, Dezhuang; Chen, Si; Chen, Hong (Frontiers in Physics, 2021)
Immune checkpoint inhibitors (ICIs) are designed to reinvigorate antitumor immune responses by interrupting inhibitory signaling pathways and promote the immune-mediated elimination of malignant cells. Although ICI therapy has transformed the landscape of cancer treatment, only a subset of patients achieve a complete response. Focused ultrasound (FUS) is a noninvasive, nonionizing, deep penetrating focal therapy that has great potential to improve the efficacy of ICIs in solid tumors. Five FUS modalities have been incorporated with ICIs to explore their antitumor effects in preclinical studies, namely, high-intensity focused ultrasound (HIFU) thermal ablation, HIFU hyperthermia, HIFU mechanical ablation, ultrasound-targeted microbubble destruction (UTMD), and sonodynamic therapy (SDT). The enhancement of the antitumor immune responses by these FUS modalities demonstrates the great promise of FUS as a transformative cancer treatment modality to improve ICI therapy. Here, this review summarizes these emerging applications of FUS modalities in combination with ICIs. It discusses each FUS modality, the experimental protocol for each combination strategy, the induced immune effects, and therapeutic outcomes.